English Language Learning System Using Web Based Rapid Application Development Method - Dani Dani (Komunitas Dosen Indonesia, 2025)
This study aims to develop an interactive and fun web-based English learning application for school Pupil. The Rapid Application Development (RAD) method is used to design this application, which combines media elements such as animation, text, audio, and images. This application is made to arouse Pupil' enthusiasm for learning, while making it easier for teachers to teach. There are various fun and interactive features in it, for example, English learning materials are packaged with an attractive appearance, as well as the ability to monitor each Pupil's learning progress. By using this application, teachers can provide initial knowledge to Pupil more effectively and monitor Pupil learning progress online. This study has succeeded in developing an effective and efficient web based English learning application in improving Pupil' abilities in learning English. The evaluation results showed that 93.77% of Pupil succeeded in improving their English learning skills, with 30 out of 32 Pupil showing increased skills and a satisfaction level of 89.2% from teachers and 89.4% from Pupil.This web-based English learning application can be an alternative in the learning process at school, improving the quality of English learning for Pupil. The RAD method is effective in developing effective and efficient learning applications. This application is expected to increase Pupil' interest in learning and be an example for other schools. This research can contribute to the development of effective and efficient web-based English learning applications, improve the quality of English learning in schools, and be a solution to improve Pupil' English learning abilities.